Solve the systems : 1) x = 3y 3x + y = 10 2)  2x + 7y = 1 2x - 2y = 9

Expert Answers

An illustration of the letter 'A' in a speech bubbles

x = 3y........(1)

3x + y = 10.........(2)

Using the substitution method, we will substitute x values from (1) in equation (2):

==> 3x + y = 10

==> 3(3y) + y = 10

==> 9x + y = 10

==> 10y = 10

==> y= 1

==> x= 3y = 3*1 = 3

==> x= 3

 

 2x + 7y = 1........(1)

2x - 2y = 9.........(2)

Using the elimination method, we will subtract (2) from (1):

==> 9y = -8

==> y= -8/9

Now to find x value , we will substitute with with either (1) or (2):

==> 2x - 2y = 9

==> 2x - 2(-8/9) = 9

==> 2x + 16/9 = 9

==> 2x = 9 - 16/9

==> 2x = 65/9

==> x= 65/18

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial